Open source for knowledge and learning management strategies beyond tools - Lytras, Miltiadēs 1973-; Naeve, Ambjörn (Idea Group Publishing, 2007)
"This book presents learning and knowledge management from a point of view where the basic tools and applications are provided by open source technologies. It explains an intense orientation to the critical issues of the open source paradigm: open source tools, applications, social networks, and knowledge sharing in open source communities" - Provided by publisher
Includes bibliographical references and index
Keywords: Knowledge management; Organizational learning; Open source intelligence; Organisatorisches Lernen; Open Source; Wissensmanagement; Aufsatzsammlung